Wound healing prospective of pongamia glabra, piper nigrum and momordica charantia on albino rats using anemic burn wound model - Shukla, Rashmi; Kashaw, Varsha (Journal of Drug Delivery and Therapeutics, 2018)
Objective: The objective of present work was to evaluate wound healing potential of pongamia glabra, piper nigrum and momordica charantia using as herbal ointment formulation on albino rats using burn wound model. All the plant has the rich source of alkaloid, glycoside, tannins, carbohydrates, saponins, flavonoids, proteins and amino acids content and were used as anti-diabetic, anti-inflammatory, antitumor, anti-malarial and having wound healing potential. Materials and Methods: Extract of all three plants has been separated by the Soxhlet extraction. Herbal ointment formulation has been prepared by mixing the extract of momordica charantia, pongamia glabra and piper nigrum with the wool fat and paraffin. Burn wound model has been utilized for the evaluation of wound healing potential. Histopathological evaluation has been also carried-out for the physical verification wound healing potential. Results and Conclusion: The studies on burn wound healing model reveals that all twelve groups showed decreased wound area on the time and there was no mortality observed in the course of study. Discussion: These studies have indicated that herbal ointment formulation of pongamia glabra, piper nigrum and momordica charantia has been utilized for wound healing and it is safer for topical application. No toxicity and mortality have been observed during the experimental tenure. Keywords: Wound healing, momordica charantia, pongamia glabra, piper nigrum, burn wound model